The Belt and Road Initiative: China-Russian Trade Development Strategy - Liu Yiwen,Irina V. Pustokhina, Denis A. Pustokhin (International Journal of Advanced Science and Technology, 2020)
As two major economic powers in the world, China and Russia maintain relatively stable and friendly cooperative relations in the political, economic and other fields. At present, Sino-Russian trade cooperation is showing positive development. The volume of trade is steadily increasing. The structure of import and export commodities is highly complementary. The areas of cooperation are expanding. The potential for trade cooperation is huge, but there is still a single structure, low added value of products, and regional trade friction problem. The two countries should firmly seize the opportunities of the Belt and Road initiative to further optimize the Sino-Russian trade structure and expand trade. In the field of trade cooperation, it is necessary to accelerate the process of establishing a free trade zone, strengthen bilateral high-level dialogues, optimize trade policies, promote the common development of the two economies, and contribute to the maintenance of regional peace and stability. This article provided an insight into the Cino-Russian trade in the context of the Belt and Road Initiative, discussed Cino-Russian trade data, analyzed the challenges and opportunities encountered by the Cino-Russian trade, and discussed the Cino-Russian trade development strategy. Finally, it is concluded that in order to promote the development of Sino-Russian trade, it requires joint efforts of both China and Russia, strengthen the standardized implementation of the trade order, cooperation and development in the financial field between China and Russia to facilitate the development of bilateral trade